Konsep Negara Hukum Dalam Perspektif Hukum Tata Negara Indonesia (The Concept Rule Of Law From The Perspective Of Indonesian Constitutional Law) - Kaban, Divany Harbina Emzilena; Putri, Keshia Annisa; Paksi, Arif Pujawangsa; Triadi, Irwan (Media Hukum Indonesia (MHI), 2024)
Almost every country has aspirations to become a rule of law state. Indonesia is no exception, with its aspiration as a rule of law state enshrined in the 1945 Constitution of the Republic of Indonesia. The concept of a rule of law state places all activities of the state and its society under the law. It also governs the administration of the state through legislation and upholds the sovereignty or supremacy of the law based on principles and values of justice. This research employs a juridical normative approach by conducting document analysis and utilizing data and information obtained through literature review. The research findings suggest that the concept of a rule of law state should be upheld because it offers the advantage of enabling the state to control society and foster justice within the nation. Furthermore, to address the shortcomings of this legal concept, it is necessary to incorporate principles and values that have developed and become integral to society, such as those embodied in Pancasila, into prevailing legislation. This ensures that legislation serves not only as a tool for those in power to govern the state but also as a manifestation of justice within society.